Fertilidade do caranguejo de mangue Ucides cordatus (Linnaeus) (Crustacea, Brachyura, Ocypodidae), em Iguape (São Paulo, Brasil) - Hattori, Gustavo Yomar [UNESP]; Pinheiro, Marcelo Antonio Amaro [UNESP] (Sociedade Brasileira de Zoologia, 2003)
A total of 58 Ucides cordatus (Linnaeus, 1763) ovigerous females in final embryonic stage were collected in mangrove forest at Iguape (São Paulo). Each female were kept in laboratory until the larvae hatching and had their carapace width (CW) measured with caliper (0.05 mm) and the larval number (LN) calculated by volumetric method. The hatching rates (HR) were calculated for each animal's size class (5 mm). The values of LN and CW obtained were subjected to regression analyses and the best fitting model was chosen by comparing the obtained determination coefficients (R²). The fertility varied from 71,200 to 220,800 larvae (147,169 ± 32,070 larvae), corresponding to 41.7 to 76.8 mm CW (63.7±7.9 mm), respectively. The relationship LNxCW was expressed by the equation LN = 284.1CW1.5º¹ (N = 58; R² = 0.74; p < 0.01), that showed a positive correlation between the variables. Most part of ovigerous females (89.7%) showed their hatching during the nightly period. A negative correlation between HR and CW was observed in these animals (p < 0.05), probably due to reduction of spermatophores in the seminal receptacle (multiparous females) or due to senility in the females with large size. The biological studies of U. cordatus are very important for practices adoption that preserve and make the rational use of this recourse in Brazilian's mangrove forests.
Fertility of the mangrove crab Ucides cordatus (Linnaeus) (Crustacea, Brachyura, Ocypodidae), at Iguape (São Paulo), Brazil
Keywords: Brachyura; Crustacea; Fertility; Ocypodidae; Reproduction; Ucides